![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2x^3y-2xy^3-4xy^2-2xy\)
\(=2xy.\left(x^2-y^2-2y-1\right)\)
\(=2xy.[x^2-\left(y^2+2y+1\right)]\)
\(=2xy.[x^2-\left(y+1\right)^2]\)
\(=2xy.\left(x+y+1\right).\left(x-y-1\right)\)
Vậy chọn đáp án A
![](https://rs.olm.vn/images/avt/0.png?1311)
2x(x-2)+2y(x-2)= (x-2)(2x+2y)=2(x-2)(x+y)
b,2(xy+xyz-2x-2z)
c, 3(x^2-xy-x-y)
a) Ta có : 2x2 - 4x + 2xy - 4y
= 2x(x - 2) + 2y(x - 2)
= (x - 2)(2x + 2y)
= 2(x - 2)(x + y)
![](https://rs.olm.vn/images/avt/0.png?1311)
21, \(x^3-4x^2+4x=x\left(x^2-4x+4\right)=x\left(x-2\right)^2\)
22, \(15x^2y+20xy^2-25xy=5xy\left(3x+4y-5\right)\)
23, \(4x^2+8xy-3x-6y=4x\left(x+2y\right)-3\left(x+2y\right)=\left(4x-3\right)\left(x+2y\right)\)
24, \(x^3-6x^2+9x=x\left(x^2-6x+9\right)=x\left(x-3\right)^2\)
Tương tự :))
21.\(x^3-4x^2+4x\)
\(=x\left(x^2-4x+4\right)\)
\(=x\left(x-2\right)^2\)
22,\(15x^2y+20xy^2-25xy\)
\(=5xy\left(3x+4y-5\right)\)
23,\(4x^2+8xy-3x-6y\)
\(=4x\left(x+2y\right)-3\left(x+2y\right)\)
\(=\left(4x-3\right)\left(x+2y\right)\)
24\(x^3-6x^2+9x\)
\(=x\left(x^2-6x+9\right)\)
\(=x\left(x-3\right)^2\)
25,\(x^2-xy+x-y\)
\(=x\left(x-y\right)+\left(x-y\right)\)
\(=\left(x+1\right)\left(x-y\right)\)
26.\(xy-2x-y^2+2y\)
\(=x\left(x-2\right)-y\left(y-2\right)\)
\(=\left(x-y\right)\left(x-2\right)\)
27,\(x^2+x-xy-y\)
\(=\left(x^2-xy\right)+\left(x-y\right)\)
\(=x\left(x-y\right)+\left(x-y\right)\)
\(=\left(x+1\right)\left(x-y\right)\)
28,\(x^2+4x-y^2+4\)
\(=\left(x^2+4x+4\right)-y^2\)
\(=\left(x+2\right)^2-y^2\)
\(=\left(x+2-y\right)\left(x+2+y\right)\)
29.\(x^2-2xy+y^2-4\)
\(=\left(x-y\right)^2-2^2\)
\(=\left(x-y-2\right)\left(x-y+2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) 2x2 - 4x = 2x( x - 2 )
2) 3x - 6y = 3( x - 2y )
3) x2 - 3x = x( x - 3 )
4) 4x2 - 6x = 2x( x - 3 )
5) x3 - 4x = x( x2 - 4 ) = x( x - 2 )( x + 2 )
1) \(2x^2-4x=2x\left(x-2\right)\)
2) \(3x-6y=3\left(x-2y\right)\)
3) \(x^2-3x=x\left(x-3\right)\)
4) \(4x^2-6x=2x\left(2x-3\right)\)
5) \(x^3-4x=x\left(x-2\right)\left(x+2\right)\)
\(a,2x^2+3x-2xy-3y\)
\(=x\left(2x+3\right)-y\left(2x+3\right)\)
\(=\left(2x+3\right)\left(x-y\right)\)
\(b,x^3-4x^2+4x\)
\(=x\left(x^2-4x+4\right)\)
\(=x\left(x-2\right)^2\)
#Urushi
a) \(2x^2+3x-2xy-3y\)
\(\text{=}2x\left(x-y\right)+3\left(x-y\right)\)
\(\text{=}\left(2x+3\right)\left(x-y\right)\)
b) \(x^3-4x^2+4x\)
\(\text{=}x\left(x^2-4x+4\right)\)
\(\text{=}x\left(x-2\right)^2\)